Peranan Budaya Organisasi dalam Kinerja Karyawan di Kawasan Wijaya Kusuma Semarang: Analisis Faktor-Faktor yang Mempengaruhi Produktivitas dan Kepuasan Kerja - Wulandari; Bonaventura Hendrawan Maranata (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
Organisational culture has a significant impact on an organisation's efficacy and durability, especially when it comes to raising employee performance. This research examines how organisational culture supports worker performance at Semarang's Wijaya Kusuma Industrial Estate (KIWK), home to a number of manufacturing and distribution businesses that must contend with fierce rivalry and constantly shifting environmental conditions. The primary topic covered is how implementing organisational cultural values influences workers' attitudes, actions, and output while assisting in the accomplishment of business objectives. The goal of the study is to determine which aspects of organisational culture are most prevalent and examine how they relate to metrics of employee performance. This study uses an ethnographic design and a qualitative methodology. Robbins' organisational culture framework and employee performance indicators served as the basis for the interview guidelines used to gather data through in-depth interviews and observations at a number of KIWK enterprises. The results show that discipline, creativity, result orientation, attention to detail, cooperation, and stability in implementing standard operating procedures (SOPs) have all been used to successfully integrate organisational culture at KIWK. The quality, quantity, timeliness, effectiveness, and independence of employee performance are all favorably impacted by these elements. The synthesis of findings suggests that consistent application of organisational culture contributes not only to higher productivity but also to the development of a supportive work environment. In conclusion, a strong, innovative, and disciplined organisational culture significantly enhances employee performance in KIWK. Therefore, management should maintain and further develop adaptive cultural values to cope with the dynamic challenges of the industrial sector.